Airway hypersensitivity induced by eosinophil granule-derived cationic proteins. (August 2019) - Lee, Lu-Yuan; Gu, Qihai; Lin, An-Hsuan; Khosravi, Mehdi; Gleich, Gerald
Abstract: Vagal bronchopulmonary C-fiber sensory nerves play an important role in the manifestation of airway hypersensitivity, a common and prominent pathophysiological feature of airway inflammatory diseases. Eosinophil granule-derived cationic proteins are known to be involved in the mucosal damage and development of bronchial hyperresponsiveness during allergic airway inflammation. In view of these background information, we have carried out a series of studies to investigate the effect of cationic proteins on these C-fiber afferents and the mechanism(s) possibly involved; a summary of these studies is presented in this mini-review. Intra-tracheal instillation of either eosinophil granule-derived (e.g., major basic protein, MBP) or synthetic cationic proteins (e.g., poly-l -lysine) induced a sporadic, but intense and lingering discharge of pulmonary C-fibers, and greatly enhanced the chemical and mechanical sensitivities of these afferents in anesthetized rats. The stimulatory and sensitizing effects of these proteins were completely nullified when their cationic charges were neutralized or removed. Furthermore, in isolated rat bronchopulmonary capsaicin-sensitive neurons, eosinophil granule cationic proteins induced a direct and long-lasting (>60 min) but reversible sensitizing effect on their responses to chemical and electrical stimulations. More importantly, our study showed that these cationic proteins exerted an inhibitory effect on the sustained delayed-rectifier voltage-gated K + current and the A-type, fast-inactivating K + current; these actions were at least in part responsible for the sensitizing effect in these neurons. In awake mice, intra-tracheal instillation of MBP also induced a slowly developing (peaking in 2–3 days), progressive and sustained (lasting for 3–7 days) elevation of the cough responses to inhaled irritant gases. Taken together, these findings suggest that the enhanced sensitivity of bronchopulmonary C-fibers induced by the eosinophil granule cationic proteins may be a contributing factor in the pathogenesis of bronchial hyperresponsiveness and chronic cough associated with eosinophilic infiltration of the airways.